Helen Lawlor, Irish Harping 1900–2010: ‘It is New Strung’ (2012) - Caldwell, Conor (Journal of the Society for Musicology in Ireland, 2014)
A review of Helen Lawlor, Irish Harping 1900–2010: ‘It is New Strung’ (Dublin: Four Courts Press, 2012). ISBN 978-1-84682-367-1.